Active layer hydrology in an arctic tundra ecosystem: quantifying water sources and cycling using water stable isotopes. Issue 26 (26th August 2016) - Throckmorton, Heather M.; Newman, Brent D.; Heikoop, Jeffrey M.; Perkins, George B.; Feng, Xiahong; Graham, David E.; O'Malley, Daniel; Vesselinov, Velimir V.; Young, Jessica; Wullschleger, Stan D.; Wilson, Cathy J.
Abstract: Climate change and thawing permafrost in the Arctic will significantly alter landscape hydro‐geomorphology and the distribution of soil moisture, which will have cascading effects on climate feedbacks (CO2 and CH4 ) and plant and microbial communities. Fundamental processes critical to predicting active layer hydrology are not well understood. This study applied water stable isotope techniques ( δ 2 H and δ 18 O) to infer sources and mixing of active layer waters in a polygonal tundra landscape in Barrow, Alaska (USA), in August and September of 2012. Results suggested that winter precipitation did not contribute substantially to surface waters or subsurface active layer pore waters measured in August and September. Summer rain was the main source of water to the active layer, with seasonal ice melt contributing to deeper pore waters later in the season. Surface water evaporation was evident in August from a characteristic isotopic fractionation slope ( δ 2 H vs δ 18 O). Freeze‐out isotopic fractionation effects in frozen active layer samples and textural permafrost were indistinguishable from evaporation fractionation, emphasizing the importance of considering the most likely processes in water isotope studies, in systems where both evaporation and freeze‐out occur in close proximity. The fractionation observed in frozen active layer ice was not observed in liquid active layer pore waters. Such a discrepancy between frozen and liquid active layer samples suggests mixing of meltwater, likely due to slow melting of seasonal ice. This research provides insight into fundamental processes relating to sources and mixing of active layer waters, which should be considered in process‐based fine‐scale and intermediate‐scale hydrologic models. Copyright © 2016 John Wiley & Sons, Ltd.